Effectiveness of glycerin-oxalic acid strips and essential oils in controlling Varroa destructor in honeybee - Hristov, Plamen Rangelov; Hristakov, Ivaylo Stefanov; Atanasov, Atanas Zdravkov; Zhelyazkov, Presiyan Antoniov (Veterinarni medicina, 2025)
The decline in the bee colony strength due to high levels of Varroa destructor infestations necessitates the development of new control methods. This study evaluates the effectiveness of glycerin-oxalic acid strips and essential oils in managing Varroa destructor. The experiment was conducted in 2022 at the experimental apiary in Debelec, part of the Institute of Animal Husbandry in Kostinbrod. Six experimental groups, each treated with a different preparation, were compared to a control group of untreated colonies. Treatments included Beevital Hiveclean (20 ml per colony), Varro Red (2 ml per frame), ammonium nitrate strips (1.3 mm), glycerin-oxalic acid strips (1.3 mm), and glycerin-oxalic acid strips of paper-cellulose (2.3 mm) or cellulose-cotton (2.3 mm). The control group remained untreated. The glycerin-oxalic acid strips made of cellulose and cotton (2.3 mm) showed the highest efficacy, reducing the mite infestation by 17.79% compared to the control. The glycerin-oxalic acid strips of paper-cellulose (2.3 mm) were also effective, achieving a 17.05% reduction in mite levels. These results provide valuable insights for beekeepers seeking alternative and sustainable methods for controlling Varroa destructor infestations.
Keywords: alternative treatment methods; apiculture health; mite infestation control; parasitic resistance